C/N ratios and carbon isotope composition of organic matter in estuarine environments - Leng, Melanie J.; Lewis, Jonathan P. (Springer Netherlands, 2017)
The sediments that are preserved in estuarine environments (saltmarsh, riverine estuaries, mangrove habitats, lagoons, isolation basins and fjords) contain organic matter that allows investigation of the provenance of that material. These data can then be used specifically to investigate past sea level/land level changes and changes in freshwater flux. Where microfossils are poorly preserved or absent, C/N and δ13C analyses offer an alternative method to deduce environmental histories, but they are especially useful when used in conjunction with a range of other proxies, and when local modern end-member organic variables can be measured to ‘calibrate’ the sedimentary C/N and δ13C. There are a wide range of C/N-δ13C based carbon studies, here we describe examples of studies in a variety of estuarine environments.